2015
DOI: 10.1039/c4rp00176a
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the properties of chromium's oxidation states with a case study method

Abstract: The purpose of this study was to investigate how a mixed-method case study affects pre-service science teachers' awareness of hexavalent chromium pollution and content knowledge about the properties of chromium's different oxidation states. The study was conducted in Turkey with 55 sophomores during the fall semester of 2013–2014. The students were taught using a case study about chromium's properties, the qualitative and quantitative analysis methods used with chromium compounds, the effects of chromium compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
1
12
0
4
Order By: Relevance
“…Gardner, 1995;Osborne et al, 2003). This may also indicate that the SSTs perceive the chemists as open-minded people (and/or flexible in their ideas) (Çalık and Coll, 2012;Çalık et al, 2014a, 2014b, 2015. Overall, it can be concluded that a positive female discrimination in National Education and a large number of inquiry-based interventions/curricula (see Çalık and Ayas, 2008;Çalık, 2014) undertaken in the 2000s seem to have accomplished the targeted goals in the case of Turkish context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gardner, 1995;Osborne et al, 2003). This may also indicate that the SSTs perceive the chemists as open-minded people (and/or flexible in their ideas) (Çalık and Coll, 2012;Çalık et al, 2014a, 2014b, 2015. Overall, it can be concluded that a positive female discrimination in National Education and a large number of inquiry-based interventions/curricula (see Çalık and Ayas, 2008;Çalık, 2014) undertaken in the 2000s seem to have accomplished the targeted goals in the case of Turkish context.…”
Section: Discussionmentioning
confidence: 99%
“…Because the Higher Education Council centrally decides the capacity of each programme (i.e. Ayyıldız and Tarhan, 2012;Hugerat and Kortam, 2014;Özdilek, 2015), context-based approach (Ültay and Çalık, 2012; Ültay et al, 2015), and technology-embedded scientific inquiry (e.g. For this reason, despite the fact that inquiry-based science teaching is theoretically expected, the overcapacity of the teacher education programmes tends to dampen the lecturers' (i.e.…”
Section: Implications For Practice and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…9,19 Todavia, a maioria dos artigos descreve a utilização do método para o desenvolvimento de habilidades necessárias aos futuros profissionais da Química, 9,[20][21][22] como uso da linguagem, 21 consciência cultural num contexto de globalização econômica, 22 assim como para a aquisição de uma maior consciência ambiental. 19 Em contrapartida, o uso da RP está mais direcionado à aprendizagem de conhecimentos científicos através da resolução de situações-problema. Nessa perspectiva de aprendizagem, um problema é entendido como uma situação que apresenta certo nível de dificuldade e para o qual não se tem de imediato uma solução.…”
Section: Resolução De Problemasunclassified
“…9,19 Todavia, a maioria dos artigos descreve a utilização do método para o desenvolvimento de habilidades necessárias aos futuros profissionais da Química, 9,20-22 como uso da linguagem, 21 consciência cultural num contexto de globalização econômica, 22 assim como para a aquisição de uma maior consciência ambiental.…”
unclassified